The impact of BMI on clinical progress, response to treatment, and disease course in patients with differentiated thyroid cancer - Gąsior-Perczak, Danuta (PLoS One, 2018)
INTRODUCTION: Obesity is a serious health problem worldwide, particularly in developed countries. It is a risk factor for many diseases, including thyroid cancer. The relationship between obesity and prognostic factors of thyroid cancer is unclear. AIMS: We sought to ascertain the relationship between body mass index (BMI) and clinicopathological features increasing the risk of poor clinical course, treatment response, and clinical outcome in patients with differentiated thyroid cancer (DTC). SUBJECTS & METHODS: The study included 1181 patients with DTC (88% women and 12% men) treated at a single center from 2000 to 2016. BMI before surgery and aggressive clinicopathological features, according to the American Thyroid Initial Risk stratification system, were analyzed. The relationship between BMI and initial risk, treatment response, and final status of the disease was evaluated, incorporating the revised 2015 American Thyroid Association guidelines and the 8(th) edition of the American Joint Committee on Cancer/Tumor-Node-Metastasis (AJCC/TNM) staging system. Patients were stratified according to the World Health Organization classification of BMI. Statistical analysis was performed using univariate and multivariate logistic regression analysis. RESULTS: Median follow-up was 7.7 years (1–16 years). There were no significant associations between BMI and extrathyroidal extension (microscopic and gross), cervical lymph node metastasis, or distant metastasis in univariate and multivariate analyses. BMI did not affect initial risk, treatment response or disease outcome. Obesity was more prevalent in men (p = 0.035) and in patients ≥55 years old (p = 0.001). There was no statistically significant relationship between BMI and more advanced TNM stage in patients ≤55 years old (stage I vs. stage II) (p = 0.266) or in patients >55 years old (stage I–II vs. III–IV) (p = 0.877). CONCLUSIONS: Obesity is not associated with more aggressive clinicopathological features of thyroid cancer. Obesity is not a risk factor for progression to more advanced stages of disease, nor is it a prognostic factor for poorer treatment response and clinical outcome.